"We were told we were going to live in houses" : relocation and housing of the Mushuau Innu of Natuashish from 1948 to 2003 - Dalsbø, Elisabeth Thørring (Universitetet i Tromsø, 2010)
The Mushuau Innu is a First Nation group who have gone from a nomadic lifestyle in the interior of Labrador to a sedentary lifestyle on the coast since their first contact with European colonizers. The Mushuau Innu has gone through three relocations in a time period of 55 years; the first move was in 1948 to the Inuit community of Nutak further north, and the second in 1967 to Utshimassit (Davis Inlet) on Iluikoyak Island, where they for the first time were to live in houses. In 2003, over thirty years after settling in Utshimassit the Mushuau Innu relocated from Utshimassit to Natuashish. The aim of this thesis is to find out the background for, and if the Innu were consulted about the relocations. Also it aims to find out if the Innu were active or passive in regards to the decision making process. This thesis argues that the Innu were relocated in 1948 and settled in 1967 based on the assimilation policy, while the last relocation was part of the general political mobilization of Aboriginal peoples. It also argues that the Mushuau Innu have made conscious decisions in regards to all three relocations, although the alternatives might have been few or none and based on false assumptions.